Pengembangan Pariwisata di Kampung Naga, Tasikmalaya, Jawa Barat - Shifa Paramitha; Gde Indra Bhaskara (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2020)
Culture has an important role in the tourism industry as one of the factors that attract tourists to visit tourist attractions. One of the cultural tourism areas in West Java is Kampung Naga in Tasikmalaya Regency. Tourism has begun in this traditional village since the 1970s, but its development can be said to be slow because many tourism principles are considered not following customary rules. Unique even though tourism development is not recognized by the community, but continues to run and also benefits the community. This study uses a qualitative method that aims to identify the development of tourism in Kampung Naga. The types of data used are quantitative data and qualitative data with data collection carried out by observation, in-depth interviews, and documentaries. The data analysis used is qualitative descriptive analysis with an inductive approach. The results of this study show that the development of tourism in Kampung Naga has reached the second stage in the theory of the tourism area life cycle. Besides, there are community organizations that in charge of tourism issues in Kampung Naga, namely the Association of Indonesian Guides. Meanwhile, there are two Regional Organizations that have authority in Kampung Naga, which are the Tourism, Youth and Sports Departement and the Education Departement. The obstacle in developing tourism in Kampung Naga is a conflict between the government and local communities regarding regulations that are not obeying the customary rules in Kampung Naga. Keyword: tourism development, cultural tourism, traditional village, development obstacle, tourism area life cycle